Relationship of metabolic syndrome and neurocognitive deficits in patients with schizophrenia. (August 2019) - Grover, Sandeep; R, Padmavati; Sahoo, Swapnajeet; Gopal, Subhashini; Nehra, Ritu; Ganesh, Arthi; Raghavan, Vijaya; Sankaranarayan, Anoop
Highlights: Patients with metabolic syndrome have significantly poorer performance in the cognitive domains of processing speed, cognitive processing and selective attention. Patients with metabolic syndrome have significantly poorer auditory and verbal memory and immediate recall memory. Higher number of abnormal components of metabolic syndrome are associated with poorer functioning in the domains of cognitive processing and selective attention, auditory and verbal memory and executive functions. Abstract: This study aimed to evaluate the association of the metabolic syndrome (MS) and its components with neurocognition among patients with schizophrenia. 121 patients with schizophrenia from an outpatient service of two psychiatric centers were assessed on a neurocognitive battery and by metabolic measures. More than half (56.2%) of the patients fulfilled the consensus criteria for MS. After controlling/adjusting for various covariates (age, education in years, duration of illness, age of onset, Positive and Negative Symptom scale score and presence of smoking status), it was found that compared to patients without MS, those with MS had significantly poorer performance "in the cognitive domains" of cognitive processing and selective attention (Stroop effect percentile; p value 0.002; effect size-0.45) and auditory and verbal memory (AVLT; p value <0.001; effect size 0.68). Patients with a higher number of abnormal parameters of MS had poorer functioning in the domains of cognitive processing and selective attention, auditory and verbal memory, and executive tasks. To conclude, this two center study suggests that MS has a negative impact on neurocognition in patients with schizophrenia. There is a need to identify and monitor metabolic abnormalities among patients with schizophrenia to minimize the negative effect of metabolic parameters on neurocognition.